Russia’s accession to the WTO: problems, solutions, and opportunities - Erokhin, Vasilii (Henry Stewart Talks, 2014)
Russia on its way to the WTO, Overview of the major trade obligations accepted by Russia, Russia’s foreign trade: outlook of the latest trends, Expected threats and opportunities of the WTO’s membership for selected Russian industries